2001
DOI: 10.1042/bss0670177
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional intracellular calcium homoeostasis: a central cause of neurodegeneration in Alzheimer's disease

Abstract: The clinical symptoms of all forms of Alzheimer's disease (AD) result from a slowly progressive neurodegeneration that is associated with the excessive deposition of ϐ-amyloid (Aϐ) in plaques and in the cerebrovasculature, and the formation of intraneuronal neurofibrillary tangles, which are composed primarily of abnormally hyperphosphorylated tau protein. The sequence of cellular events that cause this pathology and neurodegeneration is unknown. It is, however, most probably linked to neuronal signal transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 99 publications
0
23
0
Order By: Relevance
“…The neuronal toxicity of the beta amyloid and the hyperphosphorylation of tau proteins leading to the development of neurofibrillary tangles and cell death in Alzheimer's disease could be influenced by an increased intracellular Ca 2+ concentration [35]. In cultured neurons, both the direct neurotoxiciy of beta amyloid protein and the excitotoxic vulnerability were attenuated when the cells were incubated in a Ca 2+ -deprived medium, suggesting the involvement of Ca 2+ influx in this process [36].…”
Section: Is There a Class Effect For The Prevention Of Dementia?mentioning
confidence: 98%
“…The neuronal toxicity of the beta amyloid and the hyperphosphorylation of tau proteins leading to the development of neurofibrillary tangles and cell death in Alzheimer's disease could be influenced by an increased intracellular Ca 2+ concentration [35]. In cultured neurons, both the direct neurotoxiciy of beta amyloid protein and the excitotoxic vulnerability were attenuated when the cells were incubated in a Ca 2+ -deprived medium, suggesting the involvement of Ca 2+ influx in this process [36].…”
Section: Is There a Class Effect For The Prevention Of Dementia?mentioning
confidence: 98%
“…The non-BP-related effect is mediated by special characteristics that may protect the brain from cognitive damage induced by HTN. For example, CCBs that cross the BBB, such as nitrendipine, have been associated with improvement in calcium dysregulation seen in patients with cognitive decline [57][58][59]. Drugs that inhibit the renin-angiotensin-aldosterone system (RAAS), especially ARBs, may have a cognitive-specific effect on cognitive function in those with HTN via its specific antiproliferative effect on angiotensin II, antioxidant effect, or increase in nitric oxide.…”
Section: Pathophysiologymentioning
confidence: 98%
“…Ca 2ϩ i levels are maintained by voltage-, ligand-gated, or store-operated Ca 2ϩ channels on the plasmalemma and by endoplasmic reticulum (ER)-resident channels (5). Several studies have indicated that disruption of ER-regulated Ca 2ϩ i homeostasis is associated with neurotoxicity in AD (6). The ER is an important dynamic Ca 2ϩ source and sink, it regulates neurotransmitter release, synaptic plasticity, gene expression, and signal transduction to the nucleus (7).…”
Section: Disruption Of Intracellular Calcium Homeostasis Precedes Thementioning
confidence: 99%